Batman : going ape - Sutton, Laurie S.; Gordon, Steven E. (New York : Harper, 2012)
As Clark Kent interviews Bruce Wayne at the opening of a new ape exhibit at the local zoo, Gorilla Grodd breaks free with the help of a helmet that make people obey him, and the two superheroes must handle the situation.
"Batman created by Bob Kane. Superman created by Jerry Siegel and Joe Shuster."
Keywords: Superheroes -- Fiction; Adventure and adventurers -- Fiction; Superheroes -- Fiction; Adventure fiction